Baculovirus and insect cell gene expression: review of baculovirus biotechnology. - Patterson, R M (1995)
The BEVS continues to evolve as a powerful, flexible tool for molecular biology, protein function, and biomedical research. Future developments offer the promise of replacement of hazardous chemical insecticides with environmentally safe biopesticides, construction of baculovirus vectors which encode genes for specific post-translational modifications, and establishment of efficient, stably transformed insect cell lines. FDA approval of BEVS-produced products offer the prospect of new biopharmaceuticals, in particular human therapeutics and vaccines, to improve human health and increase the quality of life for millions of people.